Rhodnius stali: new vector infected by Trypanosoma rangeli (Kinetoplastida, Trypanosomatidae) - Souza Castro, Gabriela Vieira de; Lima Ribeiro, Mariane Albuquerque; Ramos, Leandro Jose; Oliveira, Jader de [UNESP]; Rosa, Joao Aristeu da [UNESP]; Aranha Camargo, Luis Marcelo; Oliveira Meneguetti, Dionatas Ulises de (Soc Brasileira Medicina Tropical, 2017)
Introduction: Rhodnius stali infection by Trypanosoma rangeli is reported in this study for the first time. Methods: The triatomines were collected from the campus of the Federal University of Acre in Rio Branco, Acre, Brazil. The identification of T. rangeli was confirmed by multiplex polymerase chain reaction. Results: The examinations of two specimens revealed R. stali infection by the epimastigote forms of T. rangeli. Conclusions: The encounter of R. stali infected by T. rangeli generates an alert for the state of Acre, since the simultaneous presence with Trypanosoma cruzi can make the differential diagnosis of Chagas disease difficult.
Keywords: Triatomines; Rangeliose; Trypanosomatids